Order from entropy: big data from FAIR data cohorts in the digital age of plant breeding - Abhishek Gogna; Daniel Arend; Sebastian Beier; Ehsan Eyshi Rezaei; Tobias Würschum; Yusheng Zhao; Jianting Chu; Jochen C. Reif (Theoretical and Applied Genetics, 2025)
Lack of interoperable datasets in plant breeding research creates an innovation bottleneck, requiring additional effort to integrate diverse datasets—if access is possible at all. Handling of plant breeding data and metadata must, therefore, change toward adopting practices that promote openness, collaboration, standardization, ethical data sharing, sustainability, and transparency of provenance and methodology. FAIR Digital Objects, which build on research data infrastructures and FAIR principles, offer a path to address this interoperability crisis, yet their adoption remains in its infancy. In the present work, we identify data sharing practices in the plant breeding domain as Data Cohorts and establish their connection to FAIR Digital Objects. We further link these cohorts to broader research infrastructures and propose a Data Trustee model for federated data sharing. With this we aim to push the boundaries of data management, often viewed as the last step in plant breeding research, to an ongoing process to enable future innovations in the field.

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Fine mapping and identification of a candidate gene for the barley Un8 true loose smut resistance gene - Wen Zang; Peter E. Eckstein; Mark Colin; Doug Voth; Axel Himmelbach; Sebastian Beier; Nils Stein; Graham J. Scoles; Aaron D. Beattie (Theoretical and Applied Genetics, 2015)

Simple additive effects are rare: a quantitative review of plant biomass and soil process responses to combined manipulations of CO 2 and temperature - Wouter I. J. Dieleman; Sara Vicca; Feike A. Dijkstra; Frank Hagedorn; Mark J. Hovenden; Klaus S. Larsen; Jack A. Morgan; Astrid Volder; Claus Beier; Jeffrey S. Dukes; John King; Sebastian Leuzinger; et al. (Global Change Biology, 2012)
In recent years, increased awareness of the potential interactions between rising atmospheric CO 2 concentrations ([ CO 2 ]) and temperature has illustrated the importance of multifactorial ecosystem manipulation experiments for validating Earth System models. To address the urgent need for increased understanding of responses in multifactorial experiments, this article synthesizes how ecosystem productivity and soil processes respond to combined warming and [ CO 2 ] manipulation, and compares it with those obtained in single factor [ CO 2 ] and temperature manipulation experiments. Across all combined elevated [ CO 2 ] and warming experiments, biomass production and soil respiration were typically enhanced. Responses to the combined treatment were more similar to those in the [ CO 2 ]‐only treatment than to those in the warming‐only treatment. In contrast to warming‐only experiments, both the combined and the [ CO 2 ]‐only treatments elicited larger stimulation of fine root biomass than of aboveground biomass, consistently stimulated soil respiration, and decreased foliar nitrogen (N) concentration. Nonetheless, mineral N availability declined less in the combined treatment than in the [ CO 2 ]‐only treatment, possibly due to the warming‐induced acceleration of decomposition, implying that progressive nitrogen limitation ( PNL ) may not occur as commonly as anticipated from single factor [ CO 2 ] treatment studies. Responses of total plant biomass, especially of aboveground biomass, revealed antagonistic interactions between elevated [ CO 2 ] and warming, i.e. the response to the combined treatment was usually less‐than‐additive. This implies that productivity projections might be overestimated when models are parameterized based on single factor responses. Our results highlight the need for more (and especially more long‐term) multifactor manipulation experiments. Because single factor CO 2 responses often dominated over warming responses in the combined treatments, our results also suggest that projected responses to future global warming in Earth System models should not be parameterized using single factor warming experiments.

Precipitation manipulation experiments – challenges and recommendations for the future - Claus Beier; Carl Beierkuhnlein; Thomas Wohlgemuth; Josep Penuelas; Bridget Emmett; Christian Körner; Hans de Boeck; Jens Hesselbjerg Christensen; Sebastian Leuzinger; Ivan A. Janssens; Karin Hansen (Ecology Letters, 2012)
Climatic changes, including altered precipitation regimes, will affect key ecosystem processes, such as plant productivity and biodiversity for many terrestrial ecosystems. Past and ongoing precipitation experiments have been conducted to quantify these potential changes. An analysis of these experiments indicates that they have provided important information on how water regulates ecosystem processes. However, they do not adequately represent global biomes nor forecasted precipitation scenarios and their potential contribution to advance our understanding of ecosystem responses to precipitation changes is therefore limited, as is their potential value for the development and testing of ecosystem models. This highlights the need for new precipitation experiments in biomes and ambient climatic conditions hitherto poorly studied applying relevant complex scenarios including changes in precipitation frequency and amplitude, seasonality, extremity and interactions with other global change drivers. A systematic and holistic approach to investigate how soil and plant community characteristics change with altered precipitation regimes and the consequent effects on ecosystem processes and functioning within these experiments will greatly increase their value to the climate change and ecosystem research communities. Experiments should specifically test how changes in precipitation leading to exceedance of biological thresholds affect ecosystem resilience and acclimation.